Kalmyks, Nogaians and Kazakhs in the system of transcivilizational interaction between the peoples of southern Russia and the transboundary Caspian region - E. U. Omakaeva; E. N. Badmaeva (Nomadic Civilization: Historical Research, 2023)
The south of Russia and the transboundary Caspian region are an important geographical and historical-cultural place in the world where there were territories of nomadic civilisation. The unique geographical location at the crossroads of roads between Europe and Asia has contributed to the development of trade routes here. The natural landscape and the way nomads farmed influenced their lifestyle and mentality. The authors look at the specifics of nomadic society using the example of the Kalmyks, Nogaians and Kazakhs. Nomadic civilisation is one of the most striking pages in the history of mankind on the path of human development. The problem of studying nomadic civilisations is one of the most topical in modern historiography and at the same time complex. Some scholars deny the role of Turkic-Mongol nomadic peoples in world history. This direction in historical scholarship, associated with the dominant role of European peoples and the one-sided underestimation of the level of development of the nomadic civilisations of the East, is called European centrism. This article deals with two important aspects: the nomadic lifestyle of the Kalmyks, Nogaansi and Kazakhs in the past and the beginning of their transition to sedentarism. The article chronologically covers the period from the second half of the 18th to the first half of the 19th century, when the history of the nomadic peoples of the Eurasian steppes was determined by certain geopolitical conditions, especially by the beginning of their integration into the Russian Empire, whose fate they largely had to share.